On The Insecurity Of Generalized (rivest-shamir-adleman) - Advance And Adaptable Cryptosystem - M.A.M. Isa; N.N.A. Rahmany; M.A. Asbullah; M.H.A. Sathar; A.F.N. Rasedee (IOP Publishing Ltd, 2024)
Indexed by Scopus/ERA